Strength and glue bond degradations of MDF and particleboard after being exposed to different environmental condition - Azry, Syeed Saiful; Md Tahir, Paridah; Ashaari, Zaidon; Saad, Mohamad Jani (2006)
The degradation of fibre-based products cannot be stopped but can only be delayed by adding additives. The strength properties of both Medium Density Fibreboard (MDF) and Particleboard will decrease parallel to the time and duration of usage due to the degradation in glue bonding. The objective of this study was to estimate the degradation of strength properties of MDF and Particleboard after being condition in an air-conditioned room and at ambient.The duration of the conditioning was three months. These studies compared different board variables (exposure condition, board thickness, resin type, board type) that affect the degradation of board strength. This study alsoexamined the effect of cold-water soaking (12,24 and 72 hours) on the strength of boards. The static bending and internal bond test were used to assess the strength properties of both panel types. The MDF and Particleboard samples were obtained from commercial plants and the test sepcimens were prepared in accordance to JIS A 5908-1994. The Modulus of Elasticity (MOE), Modulus of Rupture (MOR) and Internal Bond (IB) were determined after 0 and 3 months whereas for soaked specimens after 12, 24 and 72 hours. The results showed that all the variables studied exposure condition, board thickness, resin types and board types had great significant influence on the degradation of the board's strength properties. Among the variables studied, board types and conditioning method seems to have more dominant effect compare to resin type. Conditioning the MDF and particleboard in air-conditioned room is much better than at ambient in term of MOE, MOR and IB. The thickness of the board greatly affects the strength retention of the board when exposed either in an air-conditioned, at ambient or soaked in cold water. This shows that, the higher board thickness, the greater the degradation occured.